2012
DOI: 10.1021/ml3003617
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Controlled Release of Anticancer Drug through Double Activation of Prodrug

Abstract: We designed and synthesized a novel double activatable prodrug system (drug−linker−deactivated photosensitizer), containing a photocleavable aminoacrylate-linker and a deactivated photosensitizer, to achieve the spatiotemporally controlled release of parent drugs using visible light. Three prodrugs of CA-4, SN-38, and coumarin were prepared to demonstrate the activation of deactivated photosensitizer by cellular esterase and the release of parent drugs by visible light (540 nm) via photounclick chemistry. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 26 publications
0
65
0
1
Order By: Relevance
“…Strong fluorescence signals were observed at the tumor site at 3 h post-injection and could be maintained for up to 24 h. You et al synthesized three double activatable prodrugs of the CA-4, SN-38, and coumarin system (86a-c) that were first activated by intracellular esterase and then drug release was induced by light irradiation. 232 A photo-cleavable aminoacrylatelinker and a deactivated photosensitizer allowed the spatiotemporally controlled release of drugs by visible light irradiation. When the prodrug 86a was irradiated with very low intensity light (540 nm, 8 mW cm…”
Section: View Article Onlinementioning
confidence: 99%
“…Strong fluorescence signals were observed at the tumor site at 3 h post-injection and could be maintained for up to 24 h. You et al synthesized three double activatable prodrugs of the CA-4, SN-38, and coumarin system (86a-c) that were first activated by intracellular esterase and then drug release was induced by light irradiation. 232 A photo-cleavable aminoacrylatelinker and a deactivated photosensitizer allowed the spatiotemporally controlled release of drugs by visible light irradiation. When the prodrug 86a was irradiated with very low intensity light (540 nm, 8 mW cm…”
Section: View Article Onlinementioning
confidence: 99%
“…4043 The two functional moieties are connected with a singlet oxygen cleavable linker. Upon activation of the photosensitizer with deep tissue-penetrable visible and far-red light, the conjugate generates singlet oxygen that triggers immediate PDT damage and then cleaves the linker, releasing the chemotherapeutic drugs only at the site of illumination.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bio et al demonstrated the ability of this method to cleave the aminoacrylate linker and release of the drug in cancer cells [50]. The pharmacological effects of the released drugs (e.g., combretastatin A-4, CA4) were also demonstrated both in vitro and in vivo (Figure 7) [51].…”
Section: Laser On Laser Offmentioning
confidence: 99%